ìЖАРКОЕî НА ПíЯТУ РІЧНИЦЮ ЖОВТНЕВОЇ РЕВОЛЮЦІЇ: ДЕТАЛІ ВОЄННО-ПОЛІТИЧНОГО ПОБУТУ НА ЗАПОРІЖЖІ У 1922 РОЦІ (Zaporizhzhia Historical Review, 2021)
The author takes under consideration only one event ñ local officials holiday party ñ and claims that documents of this case make possible to argue the fact of corruption among the power nomenclature. Hence the important theses is proved: in spite of proclaimed in 1921 New Economical Policy Ukraine still lived in accordance with the military communism till at least the middle of 1923.